KONTRIBUSI KECEPATAN LARI DAN KELINCAHAN TERHADAP KECEPATAN DRIBBLING BOLA BASKET PADA PEMAIN BASKET PUTRA SMKN 3 BANJARBARU - ahmad supian (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2014)
Contribution  Of  Running  Speed  And  Agility  Against  Speed  Of Dribbling Basketball. This research aims to find out: 1) wheterthere is a contribution to the running speed against speed dribbling a basketball. 2) wheter there is a contribution towards agility speed dribbling a basketball. 3) wheter thereis a contribution of running speed and agility against the speed of dribbling a basketball on a men's basketball players SMKN 3 Banjarbaru.This research method using expost facto. The population in this study was 22 person, and sampling techniques using saturated samples that add up to 22 people. Results from: 1) indicates that there is a contribution to the running speed against speed dribbling a basketball on a men's basketball players SMKN 3 Banjarbaru 2) there is a contribution of the agility of the speed of dribbling a basketball on a men's basketball player SMKN 3 Banjarbaru. 3) there is a contribution of running speed andagilityto speed dribbling a basketball on a men's basketball playersSMKN 3 Banjarbaru Keywords: running speed, agility, and speed dribbling basketballs